Hermeneutics Principles and Processes of Biblical Interpretation - Virkler, Henry A. (Baker Academic, 2023)
Preface to the Third Edition -- 1. Introduction to Biblical Hermeneutics -- 2. The History of Biblical Interpretation -- 3. Historical-Cultural Analysis -- 4. Written Contextual Analysis -- 5. Lexical-Syntactical Analysis -- 6. Theological Analysis -- 7. Special Literary Forms and Genres -- 8. Special Literary Forms and Genres -- 9. Applying the Biblical Message -- Epilogue -- Summary -- Bibliography -- Scripture Index -- Subject Index -- Back Ad -- Back Cover.